Mutations in lozenge and D-Pax2 invoke ectopic patterned cell death in the developing Drosophila eye using distinct mechanisms. - Siddall, N.A.; Behan, K.J.; Crew, J.R.; Cheung, T.L.; Fair, J.A.; Batterham, P.; Pollock, J.A. (Development genes and evolution, 2003)
Mutations in the lozenge gene of Drosophila melanogaster elicit a pleiotropic set of adult phenotypes, including severe compound eye perturbations resulting from the defective recruitment of photoreceptors R1/6 and R7, cone and pigment cells. In this study, we show that excessive patterned apoptosis is evident at the same developmental stage in these lozenge mutants. In lozenge null mutants, apoptosis occurs prior to lozenge-dependent cell fate specification. A second gene, D-Pax2, genetically interacts with lozenge. Interestingly, D-Pax2 mutants also exhibit increased cell death, but slightly later in development than that in lozenge mutants. Although expression of the caspase inhibitor p35 eliminates death in both lozenge and D-Pax2 mutants, the lozenge mutant eye phenotypes persist because other normal Lozenge functions are still lacking. D-Pax2 eye phenotypes, in contrast, are dramatically altered in a p35 background, because cells that normally differentiate as cone and primary pigment cells are subsequently transformed into secondary pigment cells. This study leads us to propose that Lozenge, aside from its known role in gene regulation of cell-specific transcription factors, is required to contribute to the repression of cell death mechanisms, creating a permissive environment for the survival of undifferentiated cells in early eye development. Lack of lozenge expression increases the likelihood that an undifferentiated cell will initiate its default death program and die prematurely. The ectopic cell death evident in D-Pax2 mutants appears to arise from the cell fate transformation of cone cells into secondary pigment cells, either autonomously or as a result of defective signalling.